1994
DOI: 10.1111/j.1699-0463.1994.tb05225.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoantibodies in serum samples with abnormal TSH levels

Abstract: Serum samples with normal and abnormal levels of thyrotropin (TSH) were tested for thyroid autoantibodies. Thyroid peroxidase (TPO) antibodies were detected by a radioimmunoassay (RIA) and by an agglutination method, and thyroglobulin (Tg) antibodies by an agglutination method. Elevated levels of TPO antibodies were detected in 47% of samples with abnormal and in 12% of samples with normal levels of TSH (p<0.001). Sixty‐one percent of the biochemically hypothyroid and 26% of the biochemically hyperthyroid samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…From another perspective, comparing mean age between positive and negative TAI showed no significant difference between the two groups (p = 0.818), this is consistent with the study done by Poppe et al [24]. A study by Kontiainen et al found an increased prevalence of anti-TPO with age [25]. Another study by Kutteh et al demonstrated elevated antithyroid antibodies titers with age until the age range of 31-35 years, after which titers found to be decreased [26].…”
Section: Discussionsupporting
confidence: 87%
“…From another perspective, comparing mean age between positive and negative TAI showed no significant difference between the two groups (p = 0.818), this is consistent with the study done by Poppe et al [24]. A study by Kontiainen et al found an increased prevalence of anti-TPO with age [25]. Another study by Kutteh et al demonstrated elevated antithyroid antibodies titers with age until the age range of 31-35 years, after which titers found to be decreased [26].…”
Section: Discussionsupporting
confidence: 87%
“…Bjoro et al, 10 in a 20-years follow-up study found that positive anti-TPO were strongly correlated to thyroid dysfunction and the prevalence of elevated TSH was nearly 10-fold higher both in females and males with positive anti-TPO compared with subjects with negative anti-TPO. Kontiainen et al, 11 found elevated levels of anti-TPO antibody in 47% of samples with abnormal and in 12% of samples with normal levels of TSH, indicating a meaningful difference (p<0.001) and also showed that 61% of patients with hypothyroidism and 26% with hyperthyroidism contained this antibody in their sera (p<0.001).…”
Section: Discussionmentioning
confidence: 95%
“…They demonstrated that 61% of patients with hypothyroidism and 26% with hyperthyroidism had high level of this antibody. 5,12,13 Present study showed mean serum FT3, FT4 and TSH as 1.99+0.572, 1.96+0.530 and 2.49+0.869mIU/L (P-value <0.0001) respectively at confident interval 95%. Madhuvan HS et al showed mean TSH :2.71+/-1.66, T3 :1.20+/-0.52 and T4:6.92+/-1.70.…”
mentioning
confidence: 51%